Mejoramiento de vida útil de la mantequilla blanca envasada en caña guadua producida por la microempresa “Don Viterbo” - Vera Espinoza, Henry Alejandro (2021)
The research was developed with the purpose of improving the quality of the white butter produced in the “Don Viterbo” micro-company, which affects its useful life. It began with a diagnosis that allowed determining the percentage of compliance with Good Manufacturing Practices (GMP); physicochemical and microbiological analyzes were also carried out to know the factors that influence it. Corrective measures were established and applied, and a new diagnosis was made. Techniques such as observation, survey and checklist were applied, in addition to the application of the comparative method, the same that allowed to verify the quality in the useful life of the white butter from the corrective actions implemented. The results obtained showed that before the implementation of measures, the microenterprise had 36% compliance and values of humidity, acidity, mesophilic aerobes and E. coli outside the limit allowed by INEN 161, in addition, an increase in those parameters was evidenced. as the days went by. After the implementation of measures, it was achieved that the microenterprise obtained 78% compliance and through the statistical tools of T-student and binary logistic regression it was determined that the implementation favored the improvement of the quality in the physicochemical and microbiological characteristics of the product.